COVID-19 infection and its impact on case-fatality in patients with pulmonary embolism. (3rd October 2022) - Hobohm, L; Sagoschen, I; Barco, S; Farmakis, I; Fedeli, U; Koelmel, S; Gori, T; Espinola-Klein, C; Munzel, T; Konstantinides, S; Keller, K
Abstract: Background: Although a high prevalence of pulmonary embolism (PE) has been reported as a complication during severe COVID-19 infections in critical ill patients, nationwide data of hospitalized patients with COVID-19 with PE is still limited. Thus, we sought to analyze seasonal trends and predictors of in-hospital case-fatality in patients with COVID-19 and PE in Germany. Methods: We used the German nationwide inpatient sample to analyze all data on hospitalizations for COVID-19 patients with and without PE in Germany during the year 2020 and to compare changes of PE prevalence to 2019. Results: We analyzed data of 176, 137 hospitalizations because of COVID-19 in 2020. Among those, PE was recorded in 1.9% (n=3, 362) of discharge or death certificates. Almost one third of patients with COVID-19 and PE died during the in-hospital course (28.7%). The case-fatality rate increased with patients' age peaking in the 9th life-decade. Regardless of COVID-19, 196, 203 inpatients were diagnosed with PE in Germany between 2019 and 2020. The number of PE hospitalizations were widely equally distributed between both years (98, 485 vs. 97, 718), while the case-fatality rate of all patients with PE was slightly lower in 2019 compared to 2020 (12.7% vs. 13.1%, P<0.001). In contrast, considerable differences in prevalence and case-fatality were demonstrated in 2020 regarding PE patients with and without COVID-19 infection (28.7% vs. 13.1%, P<0.001) (Figure 1). A COVID-19-infection was associated with a 2.8-fold increased risk of case-fatality in patients with PE (OR 2.81, 95% CI 1.66–2.12, P<0.001). Conclusions: In Germany, the prevalence of PE events complicating hospitalizations was similar in 2019 and 2020. However, the fatality rate among patients with COVID-19-associated PE was substantially higher than that in those without either COVID-19 or PE, indicating an additive prognostic effect of these two conditions. Funding Acknowledgement: Type of funding sources: None.